Multicenter retrospective study of endoscopic ultrasound‐guided biliary drainage for malignant biliary obstruction in Japan. (11th September 2013) - Kawakubo, Kazumichi; Isayama, Hiroyuki; Kato, Hironari; Itoi, Takao; Kawakami, Hiroshi; Hanada, Keiji; Ishiwatari, Hirotoshi; Yasuda, Ichiro; Kawamoto, Hirofumi; Itokawa, Fumihide; Kuwatani, Masaki; Iiboshi, Tomohiro; et al.
Abstract Background Endoscopic ultrasound‐guided biliary drainage (EUS‐BD) is considered to be an effective salvage procedure for failed endoscopic retrograde cholangiopancreatography in patients with unresectable malignant biliary obstruction. The aim of this retrospective study was to evaluate the efficacy and feasibility of EUS‐BD. Methods From November 2006 to May 2012, a total of 64 patients who underwent EUS‐BD (44 EUS‐guided choledochoduodenostomy [EUS‐CDS] and 20 EUS‐guided hepaticogastrostomy [EUS‐HGS]) at seven tertiary‐care referral centers in Japan were included. The primary outcome was the technical success rate, and the secondary outcomes were the incidence of complications, stent dysfunction rate, time to stent dysfunction, and overall survival. Results The technical success rate for both EUS‐CDS and EUS‐HGS was 95%. The reasons for technical failure were two failed dilations of the anastomosis in EUS‐CDS and one puncture failure in EUS‐HGS. The stent dysfunction rate and 3‐month dysfunction‐free patency rate were 21% and 80% for EUS‐CDS and 32% and 51% for EUS‐HGS. There were 12 (six in EUS‐CDS and six in EUS‐HGS) procedure‐related complications (19%): five cases of bile leakage (3/2), three stent misplacements (1/2), one pneumoperitoneum (1/0), two cases of bleeding (1/1), one perforation (1/0), and one biloma (0/1). Bile leakage was more frequently observed in patients who underwent plastic stent placement (11%) than in those with covered metal stents (4%). Conclusions This Japanese multicenter study revealed a high success rate in EUS‐BD. However, the complication rate was as high as that in previous series. Covered metal stents may be useful to reduce bile leakage in EUS‐BD.